Abstracts from the seventh Australasian conference on mathematics and computers in sport (2004)
- PREDICTING WOMEN`S WORLD CUP HANDBALL MATCH OUTCOMES USING OPTIMISED RATINGS MODELS - USING PERFORMANCE OR RESULTS TO MEASURE THE QUALITY OF SPORTS COMPETITORS - THE MATHEMATICS OF BICYCLING - PART 3: THE SOMERSAULT - BOUNCING A WATER POLO BALL - A SEVEN STATE MARKOV PROCESS FOR MODELLING AUSTRALIAN RULES FOOTBALL - NOTATIONAL ANALYSIS - A MATHEMATICAL PERSPECTIVE - THE FALLACY OF THE USE OF PURE STATISTICS IN SPORT